Experiment and analysis of a leverage type stiffness controllable isolation system for seismic engineering. - Lu, Lyan-Ywan
Owing to the fixed design parameters in traditional isolation systems, the optimal isolation performance may not always be achieved when a structure is subjected to a nondesign earthquake. At the same time, even though an active isolation system (AIS) can offer a better reduction for different seismic waves, in practice the control energy required still constrains its application. To solve this problem, a novel semi-active isolation system called the Leverage type Stiffness Controllable Isolation System (LSCIS) is proposed in this paper. By utilizing a simple leverage mechanism, the isolation stiffness and the isolation period of the LSCIS can be easily controlled by adjusting the position of the pivot point of the leverage arm. The theoretical basis and the controlled law for the proposed system were first explained in this work, and then a shaking table test was conducted to verify the theory and the feasibility of the LSCIS. As shown in the experiment, the seismic behavior of the LSCIS can be successfully simulated by the theoretical model, and the isolation stiffness can be properly adjusted to reduce the seismic energy input in the LSCIS system. A comparison of the LSCIS with the other systems including passive isolation and AISs has demonstrated that based on the same limitation of base displacement, better acceleration reduction can be achieved by the LSCIS is lower than by any of the other isolation systems. In addition, the control energy required by the LSCIS is lower than that for an AIS using the traditional LQR control algorithm.
Keywords: Seismic isolation; Semi-active control; Variable stiffness; Minimum input energy; Leverage theorem; Position control; Servo motor